2019
DOI: 10.1001/jamaoncol.2019.3158
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of PBRM1 Alterations as a Marker of Immune Checkpoint Inhibitor Response in Renal Cell Carcinoma

Abstract: Nivolumab, an immune checkpoint inhibitor (ICI) targeting the programmed death-1 (PD-1) pathway, is approved for metastatic clear cell renal cell carcinoma (ccRCC). 1 Loss-of-function (truncating) mutations in PBRM1, a PBAF-complex gene commonly mutated in ccRCC, were previously associated with clinical benefit from anti-PD-1 therapy in a smaller study, 2 Herein, this association was examined in an independent cohort from a randomized clinical trial 1 to determine whether PBRM1 alterations are a marker of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 4 publications
5
161
1
1
Order By: Relevance
“…In lung adenocarcinoma, the gene most significantly mutated was KEAP1, recently associated with resistance to PD1 blockade in lung cancer (Rizvi). Alternatively, we identified mutations that are differentially present in T cell-inflamed tumors, such as PBRM1 in ccRCC, consistent previous reports (Miao et al 2018;Braun et al 2019). In metastatic melanoma, DCTN1 was found to be associated with the presence of T cell-inflammation while ITGAX (alias CD11c), is more frequently mutated in non-T cell-inflamed tumors.…”
Section: Somatic Mutations In Oncogenic Signaling Pathways Are Enrichsupporting
confidence: 90%
“…In lung adenocarcinoma, the gene most significantly mutated was KEAP1, recently associated with resistance to PD1 blockade in lung cancer (Rizvi). Alternatively, we identified mutations that are differentially present in T cell-inflamed tumors, such as PBRM1 in ccRCC, consistent previous reports (Miao et al 2018;Braun et al 2019). In metastatic melanoma, DCTN1 was found to be associated with the presence of T cell-inflammation while ITGAX (alias CD11c), is more frequently mutated in non-T cell-inflamed tumors.…”
Section: Somatic Mutations In Oncogenic Signaling Pathways Are Enrichsupporting
confidence: 90%
“…In one study, biallelic PBRM1 loss demonstrated improved OS (p=0.0074) and progression-free survival (p=0.029) compared with those without PBRM1 loss. 35 In the Checkmate 025 trial, PBRM1 loss was associated with clinical benefit to nivolumab, although the presence of PBRM1 loss alone was not sufficient for responses. 10 However, in a larger cohort of patients with mRCC, PBRM1 loss was not associated with improved OS (HR 1.37; 95% CI 0.79 to 2.4, p=0.265).…”
Section: Genetic Profilingmentioning
confidence: 99%
“…The results showed a significant correlation between PRBM1 status and response to anti-PD1 therapy, with a significant benefit both in PFS and OS in those patients harboring PBRM1 mutations (HR 0.67, 95% CI, 0.47-0.96; p = 0.03, and HR 0.65, 95% CI, 0.44-0.96; p = 0.03 respectively) compared to those with PBRM1 wild type tumors. There was no evidence of an association between PBRM1 status and clinical outcomes in the everolimus cohort [58].…”
Section: Immunotherapymentioning
confidence: 78%
“…There are studies that suggest the correlation of certain mutations with treatment outcomes [53][54][55]. According to some retrospective studies and preclinical data it seems that the mutational status of PBRM1 could have a predictive role [48,[56][57][58]…”
Section: Predictive Value Of Pbrm1 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation